2019
DOI: 10.3390/nu11020293
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Probiotics, Prebiotic Inulin-Type Fructans, and Synbiotics in Human Ulcerative Colitis: A Systematic Review and Meta-Analysis

Abstract: Studies of probiotics, fructan-type prebiotics, and synbiotics in patients with ulcerative colitis (UC) show significant heterogeneity in methodology and results. Here, we study the efficacy of such interventions and the reasons for the heterogeneity of their results. Eligible random controlled trials were collected from the PUBMED and SCOPUS databases. A total of 18 placebo-controlled and active treatment-controlled (i.e., mesalazine) studies were selected with a Jadad score ≥ 3, including 1491 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 81 publications
(121 reference statements)
0
42
0
6
Order By: Relevance
“…The second study of the same research group evaluated a 10 g administration of fructans to 67 subjects affected by mild IBD for 4 weeks, and they had no effects on F. prausnitzii and B. adolecentis, while Rhamnococcus gnavus and B. longum increased, with a significant improvement of disease symptoms [107]. Furthermore, two studies included in a recent metanalysis-one focused on prebiotics in an adult population and the other in children and young individuals-reported that the response to mesalazine is positively influenced by prebiotics through a mitigation of intestinal inflammation [141].…”
Section: Prebiotics and Gastrointestinal Disordersmentioning
confidence: 99%
“…The second study of the same research group evaluated a 10 g administration of fructans to 67 subjects affected by mild IBD for 4 weeks, and they had no effects on F. prausnitzii and B. adolecentis, while Rhamnococcus gnavus and B. longum increased, with a significant improvement of disease symptoms [107]. Furthermore, two studies included in a recent metanalysis-one focused on prebiotics in an adult population and the other in children and young individuals-reported that the response to mesalazine is positively influenced by prebiotics through a mitigation of intestinal inflammation [141].…”
Section: Prebiotics and Gastrointestinal Disordersmentioning
confidence: 99%
“…When intestinal flora is out of balance, harmful bacteria grow excessively, which leads to the occurrence of colon diseases. It has been revealed that probiotics are closely related to human health, especially the intestinal barrier (Asto et al, 2019). Therefore, the regulation of intestinal microecology is conducive to the control of development of UC.…”
Section: Introductionmentioning
confidence: 99%
“…There were six metanalyses published during the last two years [13,[69][70][71][72][73], the results of which are summarized in Table 4. The conclusions that we can draw from these metaanalyses could be the following: The administration of probiotics either alone or in combination with mesalazine could increase the rate of clinical remission of patients with UC.…”
Section: Effectiveness Of Probiotics In Ibd: Results Of the Publishedmentioning
confidence: 99%